Signal enhancement in X-ray Talbot interferometry with a pair of concave and convex parabolic phase gratings - Atsushi Momose; Pouria Zangi; Pascal Meyer; Martin Börner; Shinji Kobayashi; Yichen Fang; Ryosuke Ueda; Yoshichika Seki (Applied Physics Express)
X-ray Talbot and Talbot–Lau interferometers consisting of transmission gratings are widely used for X-ray phase imaging, which depicts soft materials. This study exploits the use of a pair of concave and convex parabolic gratings instead of a conventional rectangular phase grating to enhance the phase signal optically. To gain insight into the optimal design, signal enhancement is evaluated by directly measuring the self-image formed downstream of the pair. An increase in the differential phase signals is demonstrated as a function of the distance between the pair, and prospects for deploying this concept into a practical phase imaging technique are discussed.